Complications of autologous stem cell transplantation in multiple myeloma: results from the CALM study - Waszczuk-Gajda, Anna; Penack, Olaf; Sbianchi, Giulia; Koster, Linda; Blaise, Didier; Reményi, Péter; Russell, Nigel; Ljungman, Per; Trneny, Marek; Mayer, Jiri; Iacobelli, Simona; Kobbe, Guido; et al. (Journal of Clinical Medicine, 2022)
Background: The main goal of this post hoc analysis of the Collaboration to Collect Autologous Transplant Outcomes in Lymphoma and Myeloma (CALM) study was to evaluate the rate of short- and long-term infectious and non-infectious complications occurring after ASCT in patients with multiple myeloma (MM). Methods: The analysis included all patients with MM from the CALM study who underwent ≥1 ASCT. The primary endpoint of the analysis was to determine the rate of infectious and non-infectious complications after ASCT and to compare them in three time periods: 0-100 days, 101 days-1 year, and >1 year after the first transplant. Results: The analysis included a total of 3552 patients followed up for a median of 56.7 months (range 0.4-108.1). Complication rates decreased with the time from ASCT with 24.85 cases per 100 patient-years from day 0 to 100 days after the transplant, and <2.31 cases per 100 patient-years from the 101st day. At 100 days after ASC T, 45.7% of patients had complications, with infectious events being twice as frequent as non-infectious complications. Bacterial infections (6.5 cases per 100 patient-years, 95% CI: 6.1-7.0) and gastrointestinal complications (4.7 cases per 100 patient-years, 95% CI: 4.3-5.1) were the most common early events. The pattern of complications changed with time from ASCT. The presence of complications after ASCT was not associated with overall survival. Conclusions: Our data provide a solid basis for comparing ASCT-related complications to those caused by emerging treatments in multiple myeloma, such as CAR T-cell therapy and other immunotherapies.
Gesehen am 31.08.2022
This article belongs to the special issue "Plasma cell dyscrasias - laboratory and clinical insights"